2007
DOI: 10.1198/016214506000001022
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Seasonal Reg-ARFIMA–GARCH Models for Daily Electricity Spot Prices

Abstract: Novel periodic extensions of dynamic long memory regression models with autoregressive conditional heteroskedastic errors are considered for the analysis of daily electricity spot prices. The parameters of the model with mean and variance specifications are estimated simultaneously by the method of approximate maximum likelihood. The methods are implemented for time series of 1, 200 to 4, 400 daily price observations. Apart from persistence, heteroskedasticity and extreme observations in prices, a novel empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
134
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(139 citation statements)
references
References 33 publications
3
134
0
2
Order By: Relevance
“…Finally, Knittel and Roberts (2005) find an inverse leverage effect for electricity prices in the United States. Other studies have found similar results (see, for example, Weron 2006Weron , 2008Harris 2006;Geman and Roncoroni 2006;Koopman et al 2007;Pilipović 2007;Sotiriadis et al 2016).…”
Section: The Electricity System Price For the Nordic Spot Electricitysupporting
confidence: 59%
See 1 more Smart Citation
“…Finally, Knittel and Roberts (2005) find an inverse leverage effect for electricity prices in the United States. Other studies have found similar results (see, for example, Weron 2006Weron , 2008Harris 2006;Geman and Roncoroni 2006;Koopman et al 2007;Pilipović 2007;Sotiriadis et al 2016).…”
Section: The Electricity System Price For the Nordic Spot Electricitysupporting
confidence: 59%
“…These models fail to capture the full volatility dynamics of electricity prices as well as the price and volatility interrelationships. Another class of models introduces univariate generalized autoregressive conditional heteroscedasticity (GARCH) conditional volatility models, as well as other variations of GARCH modeling, such as exponential (EGARCH) and threshold (TGARCH) (see Chan and Gray 2006;Escribano et al 2011;Habell et al 2004;Higgs and Worthington 2005;Koopman et al 2007;Solibakke 2002). These models capture the price and volatility dynamics of electricity prices as well as price shock transmissions.…”
Section: The Electricity System Price For the Nordic Spot Electricitymentioning
confidence: 99%
“…Some other interesting studies on these stylized facts are Huisman and Mahieu (2003), Worthington et al (2005), Karakatsani and Bunn (2010), and Efimova and Serletis (2014). Finally, mean reversion is another specific characteristic of electricity prices, mainly driven by weather conditions (Koopman et al, 2007); it refers to the tendency of electricity prices to revert to a long-run level reflecting the long-run cost of electricity generation.…”
Section: Deregulation and Stylized Factsmentioning
confidence: 99%
“…Electricity spot prices differ substantially from time series of other commodities such as coal and natural gas because electricity still cannot be stored efficiently and, therefore, electricity demand has a major effect on the electricity spot price [30]. The hourly electricity spot price values are usually calculated using a volume weighted average of all trades executed through a power exchange hub and they are considered to be 24-dimensional time series [31]. The key indicator, European Energy Exchange (EEX) spot (electricity) price, fluctuates considerably during the day (Figure 1).…”
Section: Electricity Spot Pricementioning
confidence: 99%